2017
DOI: 10.1097/ccm.0000000000002723
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Point-of-Care Ultrasound Performed by Pulmonary Critical Care Physicians for Right Ventricle Assessment in Patients With Acute Pulmonary Embolism*

Abstract: This is the first study to evaluate pulmonary critical care fellows' and intensivists' use of goal-directed echocardiography in diagnosing right ventricular dysfunction in acute pulmonary embolism. Pulmonary Critical Care Medicine Fellows and intensivists made a timely and accurate assessment. Screening for right ventricular dysfunction using goal-directed echocardiography can and should be performed by pulmonary critical care physicians in patients with acute pulmonary embolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 34 publications
0
13
0
1
Order By: Relevance
“…However, multiple published studies have demonstrated that intensivists can acquire and interpret POCUS images with a high degree of accuracy after a limited amount of formal training. [1][2][3][4] In fact, in a review of malpractice cases related to POCUS, all cases stemmed from an alleged failure to perform POCUS or timely POCUS; there were no reported cases of failure to interpret or misdiagnosis. 5 Moreover, selfassessment and regulation is an integral professional responsibility of physicians.…”
mentioning
confidence: 99%
“…However, multiple published studies have demonstrated that intensivists can acquire and interpret POCUS images with a high degree of accuracy after a limited amount of formal training. [1][2][3][4] In fact, in a review of malpractice cases related to POCUS, all cases stemmed from an alleged failure to perform POCUS or timely POCUS; there were no reported cases of failure to interpret or misdiagnosis. 5 Moreover, selfassessment and regulation is an integral professional responsibility of physicians.…”
mentioning
confidence: 99%
“…Intensivists and pulmonary critical care fellows have been shown to be effective at timely RV dysfunction assessments using goal-directed ultrasound. 9 We chose one-half dose systemic tissue plasminogen activator to address both the DVT and the PE. Postthrombolysis echocardiogram showed improved RV strain, RV function, and RVSP (Discussion Video).…”
Section: Discussionmentioning
confidence: 99%
“…Bei hämodynamisch instabilen Patienten ist eine Echokardiografie indiziert, falls eine CT-A nicht unmittelbar verfügbar ist [11]. Diese kann durch entsprechend erfahrene Untersucher und bei Verfügbarkeit geeigneter Geräte auch präklinisch bereits durchgeführt werden.…”
Section: Echokardiografieunclassified